2014
DOI: 10.1017/neu.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists have a sustained stimulatory effect on corticosterone release after chronic treatment

Abstract: The increases in corticosterone release seen after acute exenatide or liraglutide treatment do not abate after 2 weeks of treatment demonstrating that tolerance does not develop towards this particular effect of GLP-1 agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…It is well established that psychological stress can accelerate cardiovascular disorder initiation and progression via either depression or activation of the hypothalamic–pituitary–adrenal feedback mechanisms . Previous studies reported that GLP‐1R agonists have a sustained stimulatory effect on neurohormone (ie, corticosterone) secretion in animals . We have shown that chronic stress markedly suppressed the plasma corticosterone level; this effect was restored by the treatment with anagliptin and exenatide.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is well established that psychological stress can accelerate cardiovascular disorder initiation and progression via either depression or activation of the hypothalamic–pituitary–adrenal feedback mechanisms . Previous studies reported that GLP‐1R agonists have a sustained stimulatory effect on neurohormone (ie, corticosterone) secretion in animals . We have shown that chronic stress markedly suppressed the plasma corticosterone level; this effect was restored by the treatment with anagliptin and exenatide.…”
Section: Discussionmentioning
confidence: 55%
“…6 Previous studies reported that GLP-1R agonists have a sustained stimulatory effect on neurohormone (ie, corticosterone) secretion in animals. 47,48 We have shown that chronic stress markedly suppressed the plasma corticosterone level; this effect was restored by the treatment with anagliptin and exenatide. Recently, we have demonstrated that chronic stress also increased plasma adrenaline and noradrenaline levels, and these changes were reversed by both drugs.…”
Section: Discussionmentioning
confidence: 96%
“…; Krass et al . ). Glucocorticoids are known to increase intestinal sodium and water absorption from small and large intestine as a result of their effect on Na + /K + ATPase, NHE3 and SGLT1 activity.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that peripheral administration of GLP-1 agonists significantly increases circulating glucocorticoid and aldosterone levels in both rodents and humans [12,13]. Our group has previously demonstrated that acute administration of a GLP-1 receptor agonist induces a significant increase in glucocorticoid levels in mice [14,15]. Furthermore, tolerance did not develop towards corticosterone release after chronic treatment with the GLP-1 receptor agonists exenatide or liraglutide [14].…”
Section: Introductionmentioning
confidence: 90%